Perthes disease - Suero Castro, Carlos; Queirolo, Jaime; Cevallos, Rodney (Cirugía del Uruguay, 1973)
The objective of this paper is to assist in early diagnosis and give sone guidelines for treatment of Perthes' disease. Clínica! aspects consist in the association between pain and claudication; characteristic elements of each of these symptoms are analyzed, stressing the limitations in interna! rotation and abduction of thigh. X-rays constitute an essential complement to clinic, permitting a detailed identification of each of the four evolutive stages of the disease: suspicion, certainty, correction and cure. Structural cure is indefectible, this is not the case with anatomical cure. Our present knowledge only enables us to attempt morphological repair of epiphysls; this can be done in two ways: 1) Degravitation of joint. 2) Positioning of epiphysis